2022
DOI: 10.1155/2022/1536881
|View full text |Cite|
|
Sign up to set email alerts
|

Intelligent Performance Evaluation of Urban Subway PPP Project Based on Deep Neural Network Model

Abstract: Neural network refers to an algorithmic mathematical model that imitates the behavioral characteristics of animal neural networks and performs distributed information processing. This kind of network depends on the complexity of the system and needs to adjust the internal node relationship, so as to achieve the purpose of processing information. With the continuous development of the economy, the transportation problem needs to be solved urgently, and the urban subway has emerged at the historic moment. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…However, most consider one aspect of PPPs' performance or have concentrated on one type of project and did not use KPIs. Fan et al (2022) used neural networks to develop an intelligent performance evaluation. Nevertheless, this research focused on urban subway PPP projects and did not consider KPIs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, most consider one aspect of PPPs' performance or have concentrated on one type of project and did not use KPIs. Fan et al (2022) used neural networks to develop an intelligent performance evaluation. Nevertheless, this research focused on urban subway PPP projects and did not consider KPIs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%